O Desenvolvimento Reflexivo do Professor - Liberali, Fernanda Coelho (The ESPecialist, 2012)
This article aims at discussing the role of the coordinator in the reflective process of teachers. We will emphasise reflection as an essential element for teachers transformation. In this study, the role of the coordinator, teacher - coordinator interaction and ways to lead onto a reflective process will be given particular importance.